Marine polysaccharides : food applications - Venugopal, V. 1942- (CRC Press, 2011)
"Consolidating the most recent information on polysaccharides and the efficient use of seafood wastes, this book discusses applications of marine polysaccharides in food product development and other areas. Chapters include isolation and characterization of chitin and its derivatives in seafood wastes, production of carrageenan, algin, agar, and fucoidan from seaweed, and the associated properties of these compounds. It discusses the potential functional roles of these polysaccharides in development of various food products, both of animal (including muscle and dairy) and vegetable origin, and their possible role as edible films and carriers of nutrients"-- Vydavatelská anotace
Keywords: mořské polysacharidy; polysacharidy; mořské rostliny; mořské řasy; mořští živočichové; potraviny; potravinářství; potravinářská aditiva; biopolymery; polysaccharides; sea plants; seaweeds; sea animals; food; food industry and trade; food additives; biopolymers; monografie; monographs